Exploring the phytochemical profile of green grasses with special reference to antioxidant properties. Issue 1 (1st January 2018) - Qamar, Aiza; Saeed, Farhan; Tahir-Nadeem, Muhammad; Hussain, Abdullah Ijaz; Niaz, Bushra; Ullah Khan, Azmat; Afzaal, Muhammad; Badar Ul Ain, Huma; Imran, Muhammad
ABSTRACT: The present study was conducted to evaluate the phytochemical profile of green grasses including barley and wheat. Green grasses were procured from Ayub Agricultural Research Institute, Faisalabad, Pakistan. All the phytochemical parameters were determined through standard methods with slight modifications. The explored parameters include proximate analysis, mineral profile, vitamin profile, and especially antioxidant profile (total phenolic contents (TPCs), free radical scavenging activity, flavonoids, and phenolic acids). The results portrayed that there was a significant difference between the proximate parameters, vitamin, and minerals profile of both barley and wheatgreen grasses. The antioxidant profile – antioxidant activity (283.5%) and free radical scavenging activity (99.29%) – of barley grass was much higher than wheatgrass. The TPCs (203.52 µmol of GAE/g) and flavonoids (161.12 μmol/L) were much higher in wheatgrass as compared to barley grass. Barley grass showed maximum contents of phenolic acids including benzoic acid (73.84 µg/g), caffeic acid (86.61 µg/g), gallic acid (6.33 µg/g), syringic acid (170.46 µg/g), p -hydroxybenzoic acid (42.52 µg/g), and Ferulic acid (1560.3 µg/g). Conclusively, barley grass showed higher antioxidant potential.